Development of low friction coatings for alsi milling - Brzezinka, Tomaz (Cranfield University, 2019)
Aluminium silicon (AlSi) alloys play an essential role in many industries because of their good machinability characteristics. However, their low degree of plasticity promotes adhesion at the tool edge during machine cutting, leading to a built-up edge (BUE) which reduces tool lifetimes, and the silicon content leads to tool abrasion. Currently, cemented carbide mill inserts coated with titanium diboride (TiB₂)offer the prospects of machining an array of structural metallic alloys including AlSi. However, the brittle nature of TiB₂ leaves it prone to extensive surface damage, particularly during the running-in stage of machining when tool adaptation takes place. An additional coating addressing abrasive wear and preventing BUE could limit TiB₂damage. Fabricating coatings of TiB₂ using arc evaporation remains challenging as an extensive cathode fracture occurs. Thus, the present work aims to address the drawbacks associated with TiB₂ by the deposition of a thin lubricious coating on top of the TiB₂.Secondly, the development of a new cathode, which would allow the deposition of TiB₂ by arc evaporation is investigated. A hybrid Physical Vapor Deposition system combining Filtered Cathodic Vacuum Arc (FCVA) and Magnetron Sputtering was developed forth is study. Three lubricious coating systems of Ti-MoS₂, single layer DLC and DLC-WS₂ were investigated as a top layer. Ti-MoS₂ was optimised for dry machining applications, and a Ti:MoS₂ ratio around 0.39 was found to prevent Al from sticking to the tool edges. The DLC and DLC-WS₂ coatings were designed for machining with coolant. In comparison to the performance of a TiB₂ benchmark, the monolayer DLC coating improved the machining length by ~60% and a two-layer DLC-WS₂ coating decreased wear rate by ~75%, having a measured coefficient of friction of 0.05. The development of TiB₂ cathodes for FCVA required a modification of the chemical composition to improve it’s sinterability and prevent cathode fracture during arc operation. A TiB₂-TiSi₂ (5 wt%)cathode ensured the best balance between arc stability and cathode utilisation while TiB₂-C(1 wt%)has provided exceptional arc stability, although the cathode utilisation was less due to the constant generation of cathode flakes.
Keywords: Solid lubricant; WS₂; DLC; TiB₂; Arc evaporation; magnetron sputtering